Minor loading vein acclimation for three Arabidopsis thaliana ecotypes in response to growth under different temperature and light regimes - Cohu, Christopher M.; Muller, Onno; Demmig-Adams, Barbara; Adams, William W. (Frontiers in Plant Science, 2013)
In light of the important role of foliar phloem as the nexus between energy acquisition through photosynthesis and distribution of the products of photosynthesis to the rest of the plant, as well as communication between the whole plant and its leaves, we examined whether foliar minor loading veins in three Arabidopsis thaliana ecotypes undergo acclimation to the growth environment. As a winter annual exhibiting higher rates of photosynthesis in response to cooler vs. warmer temperatures, this species might be expected to adjust the structure of its phloem to accommodate greater fluxes of sugars in response to growth at low temperature. Minor (fourth- and third-order) veins had 14 or fewer sieve elements and phloem tissue comprised 50% or more of the cross-sectional area. The number of phloem cells per minor loading vein was greater in leaves grown under cool temperature and high light vs. warm temperature and moderate light. This effect was greatest in an ecotype from Sweden, in which growth under cool temperature and high light resulted in minor veins with an even greater emphasis on phloem (50% more phloem cells with more than 100% greater cross-sectional area of phloem) compared to growth under warm temperature and moderate light. Likewise, the number of sieve elements per minor vein increased linearly with growth temperature under moderate light, almost doubling over a 27°C temperature range (21°C leaf temperature range) in the Swedish ecotype. Increased emphasis on cells involved in sugar loading and transport may be critical for maintaining sugar export from leaves of an overwintering annual such as A. thaliana, and particularly for the ecotype from the northern-most population experiencing the lowest temperatures.